A commentary on Herodotus books I-IV - Asheri, David,‪ 1925-2000 (Oxford University Press, 2011)
"This commentary by leading Western scholars, originally published in Italian under the auspices of the Fondazione Lorenzo Valla, has been fully revised by the original authors and has now been edited for the English-speaking world. It is designed for use alongside the Oxford Classical Text of Herodotus, and will replace the century-old historical commentary of How and Wells (1912) as the most authoritative account of a modern scholarship on Herodotus." -- BOOK JACKET.